The Influence of Product Quality and Brand Image on Purchase Decisions of Wardah Sunscreen through Trust as a Mediating Variable in Mataram City - Samara Kartika Cinta; Didy Ika Supryadi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of product quality and brand image on purchase decisions of Wardah Sun Care products in Mataram City and to examine the role of consumer trust as a mediating variable. This research employs a quantitative approach using primary data collected from 100 respondents who have purchased or used Wardah Sun Care products. The sampling technique applied is purposive sampling, and data analysis was conducted using the Partial Least Squares (PLS) method. The results indicate that product quality does not have a significant effect on either purchase decisions or consumer trust. Conversely, brand image has a significant influence on purchase decisions but does not significantly affect trust. Another finding reveals that purchase decisions significantly influence consumer trust, suggesting that post-purchase experiences are a key factor in building trust. Overall, the findings highlight that brand image plays a crucial role in encouraging purchase decisions, while trust is primarily shaped through product usage experiences. This study provides managerial implications for Wardah to strengthen its brand image and enhance consumer experience quality to foster long-term trust.